A Soybean Pod Accuracy Detection and Counting Model Based on Improved YOLOv8 - Xiaofei Jia; Zhenlu Hua; Hongtao Shi; Dan Zhu; Zhongzhi Han; Guangxia Wu; Limiao Deng (Agriculture)
The number of soybean pods is a key determinant of soybean yield, making accurate detection and counting essential for yield estimation, cultivation management, and variety selection. Traditional manual counting methods are labor-intensive and time-consuming, and while object detection networks are widely applied in agricultural tasks, the dense distribution and overlapping occlusion of soybean pods present significant challenges. This study developed a soybean pod detection model, YOLOv8n-POD, based on the YOLOv8n network, incorporating key innovations to address these issues. A Dense Block Backbone (DBB) enhances the model’s adaptability to the morphological diversity of soybean pods, while the Separated and Enhancement Attention Module (SEAM) in the neck section improves the representation of pod-related features in feature maps. Additionally, a Dynamic Head increases the flexibility in detecting pods of varying scales. The model achieved an average precision (AP) of 83.1%, surpassing mainstream object detection methodologies with a 5.3% improvement over YOLOv8. Tests on three public datasets further demonstrated its generalizability to other crops. The proposed YOLOv8n-POD model provides robust support for accurate detection and localization of soybean pods, essential for yield estimation and breeding strategies, and its significant theoretical and practical implications extend its applicability to other crop types, advancing agricultural automation and precision farming.